Exposure to Subclinical Doses of Fumonisins, Deoxynivalenol, and Zearalenone Affects Immune Response, Amino Acid Digestibility, and Intestinal Morphology in Broiler Chickens - Revathi Shanmugasundaram; Laharika Kappari; Mohammad Pilewar; Matthew K. Jones; Oluyinka A. Olukosi; Anthony Pokoo-Aikins; Todd J. Applegate; Anthony E. Glenn (Toxins)
Fusarium mycotoxins often co-occur in broiler feed, and their presence negatively impacts health even at subclinical concentrations, so there is a need to identify the concentrations of these toxins that do not adversely affect chickens health and performance. The study was conducted to evaluate the least toxic effects of combined mycotoxins fumonisins (FUM), deoxynivalenol (DON), and zearalenone (ZEA) on the production performance, immune response, intestinal morphology, and nutrient digestibility of broiler chickens. A total of 960 one-day-old broilers were distributed into eight dietary treatments: T1 (Control); T2: 33.0 FUM + 3.0 DON + 0.8 ZEA; T3: 14.0 FUM + 3.5 DON + 0.7 ZEA; T4: 26.0 FUM + 1.0 DON + 0.2 ZEA; T5: 7.7 FUM + 0.4 DON + 0.1 ZEA; T6: 3.6 FUM + 2.5 DON + 0.9 ZEA; T7: 0.8 FUM + 1.0 DON + 0.3 ZEA; T8: 1.0 FUM + 0.5 DON + 0.1 ZEA, all in mg/kg diet. The results showed that exposure to higher mycotoxin concentrations, T2 and T3, had significantly reduced body weight gain (BWG) by 17% on d35 (p < 0.05). The T2, T3, and T4 groups had a significant decrease in villi length in the jejunum and ileum (p < 0.05) and disruption of tight junction proteins, occludin, and claudin-4 (p < 0.05). Higher mycotoxin groups T2 to T6 had a reduction in the digestibility of amino acids methionine (p < 0.05), aspartate (p < 0.05), and serine (p < 0.05); a reduction in CD4+, CD8+ T-cell populations (p < 0.05) and an increase in T regulatory cell percentages in the spleen (p < 0.05); a decrease in splenic macrophage nitric oxide production and total IgA production (p < 0.05); and upregulated cytochrome P450-1A1 and 1A4 gene expression (p < 0.05). Birds fed the lower mycotoxin concentration groups, T7 and T8, did not have a significant effect on performance, intestinal health, and immune responses, suggesting that these concentrations pose the least negative effects in broiler chickens. These findings are essential for developing acceptable thresholds for combined mycotoxin exposure and efficient feed management strategies to improve broiler performance.